Vibrational spectrum renormalization by enforced coupling across the van der Waals gap between MoS2 and WS2 monolayers - Fan, Wen (2016)
At the few or monolayer limit, layered materials define an interesting two-dimensional system with unique electronic and phonon properties. The electron band structure of monolayers can be drastically different from multilayers despite the weak van der Waals interaction between neighboring layers. In this Rapid Communication, we demonstrate that vibrational spectra of a MoS2 monolayer and a WS2 monolayer are also renormalized when the interaction between them is artificially modulated. This is achieved by using a diamond-anvil cell to apply high pressures, up to 39 GPa onto WS2/MoS2 heterobilayers. With increasing pressure, the out-of-plane Raman frequencies of the two individual monolayers repel each other, exhibiting coherent vibrations across the van der Waals gap with an optical-like and an acousticlike interlayer vibration mode. The discovery shows a crossover in lattice vibration from a two-dimensional system toward a three-dimensional system driven by enforced interlayer coupling.